Organic Houttuynia cordata Thunb harbors higher abundance and diversity of antibiotic resistance genes than non-organic origin, suggesting a potential food safe risk. (June 2019) - Xiang, Wenliang; Lu, Kekun; Zhang, Nandi; Lu, Qianwen; Xu, Qin
Abstract: The organic agricultural products has been growing rapidly in recent years. However, a potential food safe risk, resulted by introduction more antibiotic resistant genes (ARGs) accompanied with animal manure using to organic farming, has long been overlooked. In current study, the bacterial community, 22 tetracycline, 3 aminoglycoside and 4 β-lactams ARGs were respectively investigated in the organic, chemical and wild Houttuynia cordata Thunb (HCT). A total of 9 tetracycline, 3 aminoglycoside and 2 β-lactam ARG subtypes were detected, and the organic HCT harbored more ARG subtypes. The absolute and relative abundance of total ARGs in organic HCT was strikingly higher than that in chemical and wild HCT. The Enterobacteriaceae, Aeromonadaceae, Pseudomonadceae, Moraxellaceae and Oxalobacteraceae were the dominant taxa in the chemical and wild HCT, but in the organic HCT, only Enterobacteriaceae posed 83.23% - 87.40% of bacterial community. Fourteen bacterial families might be the possible hosts of ARG subtypes in the HCT. Enterobacteriaceae was a possible host of most ARG subtypes, including tet A, tet B, tet C, tet E and aad A, and it was the main bacteria affecting the behavior of ARGs in the HCT. Additionally, the tetracycline ARG subtypes had more possible hosts. These results help to better understand the ARG potential food safe risk and develop effective measures to prevent the ARG dissemination in organic agricultural product. Graphical abstract: Unlabelled Image Highlights: Organic HCT harbored significantly higher diversity and abundance of ARGs. Tetracycline ARG subtypes were most frequently detected in organic HCT. Enterobacteriaceae was an important host taxa carrying most diverse ARG subtypes. The higher prevalence of ARGs in organic HCT suggested a potential food safe risk.